2009
DOI: 10.1007/s00441-009-0854-2
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and morphological characteristics of the interstitial cells of Cajal in the ileocaecal junction of the guinea-pig

Abstract: The guinea-pig ileocaecal junction including the valve was studied by immunohistochemistry to clarify the organization of the muscle bundles, the enteric nerves and the interstitial cells of Cajal (ICC). This region clearly exhibited characteristic features in the distribution patterns of ICC in a proximal to distal direction: (1) the thickened portion of the terminal ileum immediately adjacent to the ileocecal junction contained many ICC throughout the circular (ICC-CM) and longitudinal (ICC-LM) muscle layers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
(32 reference statements)
2
7
0
Order By: Relevance
“…The ileum protruded into the cecum, as reported [4] , who used human ICJ samples and reported that the muscle layers of the ileum and large intestine extended into the ileal papilla. In this study, we observed a thickening and narrowing of the smooth muscle layer in both groups, as reported [1][2][3][4]10] . Histologically, the elderly group exhibited a condensation of the connective tissue between smooth muscle cells in the transition; however, the young group displayed noticeable gaps between the smooth muscle fibers, which likely indicate limited development of collagen fibers.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…The ileum protruded into the cecum, as reported [4] , who used human ICJ samples and reported that the muscle layers of the ileum and large intestine extended into the ileal papilla. In this study, we observed a thickening and narrowing of the smooth muscle layer in both groups, as reported [1][2][3][4]10] . Histologically, the elderly group exhibited a condensation of the connective tissue between smooth muscle cells in the transition; however, the young group displayed noticeable gaps between the smooth muscle fibers, which likely indicate limited development of collagen fibers.…”
Section: Discussionsupporting
confidence: 68%
“…There were foramens and laminar projections of collagen fibers in the ileum ( Figure 5C and D); however, the cecal The results for elaunin, which were obtained from samples stained with resorcin-fuchsin (Weigert), showed that the average linear density was 0.00692 ± 0.00015/ value of 20876.9 ± 60.4 pixels, a significant decrease of 3.8% (P < 0.001) compared to the young group ( Figure 6A). i.e., two circular muscle layers and a longitudinal layer, as also observed [10] . In the transition region, there was a thickening of the circular muscle layer, as previously observed [4] .…”
Section: Semsupporting
confidence: 61%
See 1 more Smart Citation
“…In contrast to the ICC-SP of the stomach (Kunisawa and Komuro 2008), ileocaecal junction (Miyamoto-Kikuta et al 2009) and caecum (Tamada and Komuro 2011), ICC-SP and their processes in the proximal colon have been frequently observed in wide connective tissue spaces away from the submucosal ganglia. Basket-like structures composed of multipolar ICC-SP have been observed around the submucosal ganglia in the caecum of the guinea pig but these structures have not been observed in the proximal colon.…”
Section: Discussionmentioning
confidence: 97%
“…Recent studies have identified another ICC subtype associated with the submucosal plexus (ICC-SP) in the stomach (Kunisawa and Komuro 2008) and in the ileocaecal junction (Miyamoto-Kikuta et al 2009) of the guinea-pig. This unique ICC subtype is suggested to be involved in mucosal activity such as the secretion, absorption and transportation of fluids.…”
Section: Introductionmentioning
confidence: 98%